Why Are Children So Distractible? Development of Attention and Motor Control From Childhood to Adulthood. Issue 4 (7th April 2021) - Hoyer, Roxane S.; Elshafei, Hesham; Hemmerlin, Julie; Bouet, Romain; Bidet‐Caulet, Aurélie
Abstract : Distractibility is the propensity to behaviorally react to irrelevant information. Although children are more distractible the younger they are, the precise contribution of attentional and motor components to distractibility and their developmental trajectories have not been characterized yet. We used a new behavioral paradigm to identify the developmental dynamics of components contributing to distractibility in a large cohort of French participants balanced, between age groups, in gender and socioeconomic status ( N = 352; age: 6–25). Results reveal that each measure of these components, namely voluntary attention, distraction, impulsivity, and motor control, present a distinct maturational timeline. In young children, increased distractibility is mostly the result of reduced sustained attention capacities and enhanced distraction, whereas in teenagers, it is the result of decreased motor control and increased impulsivity.